Hydrothermal treatment of rough rice: effect of processing conditions on product attributes - Bello, Marcelo O. (2015)
A method involving hydration, tempering and heating steps is presented to process rough rice as alternative to traditional parboiling with pressure steam. The effects of temperature (66–84 °C), tempering time (60–420 min) and heating time (30–180 min) on gelatinization degree and milling yield were analyzed by response surface method (RSM). A maximum value of gelatinization degree (37.0 %) and milling yield of 67.7 % were reached with a process temperature of 84 °C using tempering and heating times of 178 and 104 min respectively. A slight reduction of crystallinity (14 %) and a significant improvement of nutritional value with increments of 150 and 60 % in riboflavin and calcium contents were obtained in comparison with control (untreated rice). Hardness and adhesiveness of processed rice were intermediate between those of control and completely gelatinized rice. The proposed method, with lower temperature requirements than traditional parboiling, is presented to obtain an alternative product, expanding consumer choices.